Republic of Lithuania : 2013 Article IV Consultation: Staff Report, Information Annex, Public Information Notice, Statement by the Executive Director. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2013)
This 2013 Article IV Consultation IMF staff report focuses on measures that are being undertaken to rebalance macroeconomic growth in Lithuania. The IMF report discusses the requirement of fiscal consolidation to fully rebuild fiscal space. It highlights the important role played by the financial sector in enabling sound credit expansion to support economic growth. Reducing obstacles to the resolution of nonperforming loans could help ease constraints on credit supply. The current account deficit is projected to remain relatively contained over the medium term, reaching about 2 percent of GDP, and financed mostly by foreign direct investment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet